ANALYSIS OF CLASS I NON TPI BEKASI IMMIGRATION OFFICE WEBSITE USING WEBQUAL 4.0 AND IPA (IMPORTANCE PERFORMANCE ANALYSIS) METHODS - Mila Rosmaya; G.A Nursanto; D.D Beyani (Polteknik Imigrasi, 2022)
The Covid-19 pandemic has forced the public to follow the sophistication of technological developments, including activities in government public services.The website is one of the media that utilizes the internet and is used in disseminating information to the public. This study aims to determine the suitability of the Bekasi Immigration Office website with the standardization of the Ministry of Law and Human Rights' website and to obtain a website service quality value using the webqual 4.0 and IPA (Importance Performance Analysis) methods. The method used in this study is to do a qualitative and quantitative approach. The standardization of Kemenkumham pages consists of domain naming, display standards, accessibility, information interoperability, social media accounts and search engine optimization, in conjunction with webqual 4.0 method, there are three research variables, namely usability, information quality, and interaction quality. There are 100 respondents in the study. Results of the research, there are six categories of suitability for standardization that have not been fulfilled on the Kanim Bekasi website. Meanwhile website correlation index is good and the results of the IPA Cartesian diagram still have top priority indicators whose performance has not been maximized and it is necessary to improve each category and indicator which is deemed not sufficient to meet the expectations or interests of users.